Lead astray: The potentials and pitfalls of lead isotopes in a New Zealand colonial burial context. (April 2020) - King, Charlotte L.; Petchey, Peter; Buckley, Hallie R.; Girvan, Elizabeth; Kinaston, Rebecca; Nowell, Geoff M.
Highlights: Lead isotopes in dental enamel were analysed from a colonial New Zealand cemetery. Lead alloy coffin strips have introduced UK lead into the NZ burial context. This is burial customs may mask isotopic evidence for human migration. Abstract: Lead isotopes can be used to identify migrants in archaeological sites, and are particularly useful when individuals may have migrated from areas of high anthropogenic or environmental lead into lower-lead concentration environments. For this reason they are ideal for identifying first European settlers (coming from a UK Industrial Revolution context) to colonies such as New Zealand. In this study, however, we highlight how ornate Victorian burial practices may introduce lead into the burial environment. This introduced lead masks the in vivo lead isotope ratios, negating its use as an indicator of foreign origins. We show that pressed pewter (tin-lead alloy) coffin strips at the colonial site of St. John's Milton (SJM) render all individuals isotopically "European", despite all children at the site having been born in New Zealand.